PERIODICITY OF LUMINOSITY OF QUASARS AND GALAXIES AT COSMOLOGICAL SCALE - Miroshnichenko, A. P. (Одеські астрономічні публікації, 2017)
We found the cosmological luminosity periodicity in decametric and optical ranges on basis of spectral analysis of luminosity distribution in quasar and galaxy samples. Comparison with known redshift periodicity for quasars and galaxies is made. Characteristic scales of luminosity periodicity are conformable to cell structure of the Universe and to activity recurrence of object nuclei.